Promotion of physical activity-related health competence in physical education: A person-oriented approach for evaluating the GEKOS intervention within a cluster randomized controlled trial. (February 2022) - Rosenstiel, Stephanie; Volk, Carmen; Schmid, Julia; Wagner, Wolfgang; Demetriou, Yolanda; Höner, Oliver; Thiel, Ansgar; Trautwein, Ulrich; Sudeck, Gorden
A central goal of physical education (PE) is to empower students to be physically active in a health-enhancing way. Therefore, using a competence-based approach, the objective of the health- and fitness-related PE intervention 'Promotion of physical activity-related health competence in PE' (GEKOS) was to address practical and theoretical content regarding training, fitness, and health. The aim of this person-oriented study was to examine differential effects of the GEKOS intervention on control competence and related knowledge, skills, abilities, and motivation. A total of 860 ninth graders were randomly assigned to an intervention or control group. Intervention group students received six PE lessons that combined practical and theoretical content regarding training, fitness, and health. Measurements were taken before, directly after, and with a follow-up after 8–12 weeks. Students completed a knowledge test and a fitness test, and filled out scales considering motivation and perceived control competence. Latent profile analysis and multinomial logistic regression were estimated. Five patterns of outcome measures were found. Intervention group students transitioned significantly more often to patterns with improved outcome values. The intervention was especially effective for a subgroup of students who initially had rather low outcome values. For a small proportion of students, the intervention entailed a loss of health-related motivation. The study indicated that students with low control competence and related knowledge, skills, abilities, and motivation can benefit from the GEKOS intervention. Future studies should investigate modes of actions and interventions that explicitly address motivation and vary the content and methods used in PE.